Intracytoplazmatická injekce (ICSI) s epididymálními a testikulárními spermiemi - Mardešić, Tonko; Hüttelová, Renata; Zetová, L; Sobotka, V; Miková, M; Müller, P; Vobořil, J; Hulvert, J (Česká gynekologie, 1997)
Azoospermia is no longer a clear indication for using donor sperm. Aspiration of epididymal sperm or extraction of testicular sperm offers the same hope of pregnancy as ICSI using ejaculated sperm. Not even the high effectivenet8 of ICSI should be the reason for less intensive efforts to assess the exact cause of azoospermia, in particular with regard to genetic aspects. This work was supported by the Grant Agency of the Ministry of Health of the Czech Republic grant No. 3050-2.
Keywords: Spermatozoa; injekce; dospělí; infertilita; lidé; mužské pohlaví; Male; Injections; spermie; Adult; Infertility; Humans